Reverse Osmosis Concentrate: Physicochemical Characteristics, Environmental Impact, and Technologies - Saavedra-Fenoglio, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This study’s aim is to generate a complete profile of reverse osmosis concentrate (ROC), including physicochemical characteristics, environmental impact, and technologies for ROC treat-ment, alongside element recovery with potential valorization. A systematic literature review was used to compile and analyze scientific information about ROC, and systematic identification and evaluation of the data/evidence in the articles were conducted using the methodological principles of grounded data theory. The literature analysis revealed that two actions are imperative: (1) coun-tries should impose strict regulations to avoid the contamination of receiving water bodies and (2) desalination plants should apply circular economies. Currently, synergizing conventional and emerging technologies is the most efficient method to mitigate the environmental impact of desalination processes. However, constructed wetlands are an emerging technology that promise to be a viable multi-benefit solution, as they can provide simultaneous treatment of nutrients, metals, and trace organic contaminants at a relatively low cost, and are socially accepted; therefore, they are a sustainable solution. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.